Integrated Nutrient Management and Continuous Cropping on Important Physical Properties of Soil in Terraced Land - Dutta, Manoj; Yhome, Vizokhonyu (International Journal of Bio-resource and Stress Management, 2023)
Twelve treatments involving N, P and K (NPK) fertilizers, farmyard manure (FYM), poultry litter, forest litter, Azospirillum and Zn either alone or in various combinations were applied continuously for nine years to evaluate the effect of integrated nutrient management practices on important soil physical properties in a terraced land. The percent aggregates >0.25 mm and mean weight diameter (MWD) increased significantly in all the treatments whereas, water holding capacity (WHC) and hydraulic conductivity increased significantly in all the treatments except ½N + PK and Forest litter burned + ½ FYM over control. The bulk density in NPK + FYM, NPK + Poultry litter, NPK + Forest litter and NPK + FYM + Zn decreased significantly (6.2, 4.6 5.4,and 10.0%, respectively) as compared to addition of NPK alone. Addition of FYM, poultry litter and forest litter with NPK increased 9.8, 16.7 and 5.1% in aggregates >0.25 mm, respectively as compared to NPK alone. Increase in MWD in different nutrient management practices ranged from 54.4 to 163.6%. The integrated application of poultry litter or FYM along with NPK was more effective in enhancing MWD.